Fixed‐point theorems for weak (ψ, β)‐mappings satisfying generalized C‐condition and its application to boundary value problem. Issue 4 (6th June 2019) - Gupta, Vishal; Mani, Naveen; Sharma, Naveen
Abstract : In this paper, we define a generalized C ‐condition and prove a fixed‐point theorem for weak ( ψ, β )‐contraction in partially ordered metric spaces. Our result extends the result of Suzuki (Proc. of the 8th Int. Conf. of Fixed Point Theory and Its Appl. 2007;65:751‐761) and Gupta and Mani ( Funct Anal Theory Methods Appl . 2017;3:26‐34). As an application, existence and uniqueness of solution of first‐order periodic boundary value problem have been given in support of our finding.